Topotaxial Phase Transformation in Cobalt Doped Iron Oxide Core/Shell Hard Magnetic Nanoparticles - López-Ortega, Alberto; Lottini, Elisabetta; Bertoni, Giovanni; de Julián Fernández, César; Sangregorio, Claudio (Chemistry of materials, 2017)
Core–shell nanoparticles based on a Co x Fe1–x O rock-salt core, and on a shell corresponding to cubic spinel Co x Fe3–x O4, have been systematically annealed to completely oxidize and generate the fully ferrimagnetic cobalt ferrite structure. The annealing has been performed through a solvent-mediated process at high temperatures to avoid interparticle aggregation, usually observed in classical annealing methods. We carefully describe how the oxidative process occurred during the initial shell passivation and in the following O2 mediated oxidation. It has been found that the rock-salt to spinel transformation occurs via topotaxial growth over the (200)RS//(400)S and (220)RS//(440)S planes shared between the two structures. This chemical transformation depends on the amount of divalent cobalt atoms present in the oxide structures. Within this respect, the solvent-mediated annealing process permits the release of a small amount of divalent cations, which allows the stoichiometry rearrangement required to form the spinel phase. The growth occurs through a topotaxial process, which involves the formation of a mosaic texture of small spinel subdomains, separated by antiphase boundaries, into the well-defined rock-salt structure along the nanoparticles. The existence of antiphase boundaries gives rise to the presence of exchange bias phenomena even for completely oxidized nanoparticles. The exchange bias effect increases the energy product of these nanocomposites, which makes this approach appealing for the realization of a novel class of free rare-earth permanent magnets.